PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA BEBERAPA JURNAL, STUDI META ANALISIS - Vani, Gracia Chou; Budiman, Felicia Alma; Natania, Clarissa -; Meiden, Carmel - (Universitas Madura, 2023)
The aim of this research is to know the impact of Good Corporate vernance on company value by used meta-analysis method from several journal. This research will provide consistent and inconsistent results with different levels of significance. Company value shows company success rate that associated with the stock price. Systematic literature review method is used. The period of this research is 2012 - 2022. The sampling technique was carried out using a purpose-driven sampling method which resulted in 24 journal samples. To know the impact of good corporate governance on company value, researcher tested and used the independent variables of the board of directors, audit committee, independent board of commissioners, institutional ownership, managerial ownership, and firm size. The result shows that a variable board of directors, audit committee, independent board of commissioners, institutional ownership, managerial ownership have an impact for company value. Firm size has no impact for company value.